The Difficulties of Determining Main Idea on Students Reading Comprehension - Fuqaha', Ansharul; Wartim, Wartim (Universitas Siliwangi, 2023)
This study used a descriptive-qualitative method using three data collection procedures to collect research data. The instruments used in this present research are observation, interviews, and documentation. This study has two research objectives. The first goal is to comprehend the challenges English students at an institute in East Java, Indonesia, face in identifying the main ideas in student reading comprehension. The second goal is to comprehend the factors that affect English language learners’ struggles in identifying the main ideas of their reading comprehension. Based on observations, interviews, and documentation, there are two difficulties in determining the main idea in students’ reading comprehension that English learners face: the first is that there is a difference between the main idea and the topic sentence, and the second is an inductive paragraph. Based on the research results of the study, some factors influence the difficulty in determining the main ideas for English learners, among which are a lack of vocabulary, reading style, and material themes. Keywords: Main Idea; Topic Sentence; Reading Comprehension.